Impact of spot reduction on the effectiveness of rescanning in pencil beam scanned proton therapy for mobile tumours. (7th November 2022) - Bertschi, Stefanie; Krieger, Miriam; Weber, Damien C; Lomax, Antony J; van de Water, Steven
Abstract: Objective . In pencil beam scanning proton therapy, individually calculated and positioned proton pencil beams, also referred to as 'spots', are used to achieve a highly conformal dose distributions to the target. Recent work has shown that this number of spots can be substantially reduced, resulting in shorter delivery times without compromising dosimetric plan quality. However, the sensitivity of spot-reduced plans to tumour motion is unclear. Although previous work has shown that spot-reduced plans are slightly more sensitive to small positioning inaccuracies of the individual pencil beams, the resulting shorter delivery times may allow for more rescanning. The aim of this study was to assess the impact of tumour motion and the effectiveness of 3D volumetric rescanning for spot-reduced treatment plans. Approach. Three liver and two lung cancer patients with non-negligible motion amplitudes were analysed. Conventional and probabilistic internal target volume definitions were used for planning considering single or multiple breathing cycles respectively. For each patient, one clinical and two spot-reduced treatment plans were created using identical field geometries. 4D dynamic dose calculations were then performed and resulting target coverage (V95%), dose homogeneity (D5%–D95%) and hot spots (D2%) evaluated for 1–25 rescans. Main results . Over all patients investigated, spot reduction reduced the number of spots by 91% in comparison to the clinical plan, reducing field delivery times by approximately 50%. This reduction, together with the substantially increased dose per spot resulting from the spot reduction process, allowed for more rescans in the same amount of time as for clinical plans and typically improved dosimetric parameters, in some cases to values better than the reference static (3D calculated) plans. However, spot-reduced plans had an increased possibility of interference with the breathing cycle, especially for simulations of perfectly repeatable breathing. Significance. For the patients analysed in this study, spot-reduced plans were found to be a valuable option to increase the efficiency of 3D volumetric rescanning for motion mitigation, if attention is paid to possible interference patterns.